Cognitive processes and reading performance - Tapia M., Violeta (2008)
This study had the objective to analyze the mental processes in terms of the thinking abilities and the cognitive functions as well as some levels of text processing that distinguish (differentiate) good and poor reader students from High School. The analysis was based on the theories: The Structural Cognitive Modifiability of Reuven Feuerstein and the Text Processing of W. Kintsch and T.A Van Dick. The cognitive demands of solution from each one of the questions of a standardized reading test were analyzed as mentioned before. The following cognitive processes were identified and organized: Classification, Analysis-Synthesis, Logic inference and Hypothetical reasoning.